(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis is devoted to the issue of developing children’s communicative competences in preschool educational institutions. The study substantiates that the formation of communication skills in preschool age is an important factor in the personal, social and intellectual development of a child. The role of the pedagogical environment, game activities, interaction with educators and peers in the development of communicative competence is analyzed. Also, pedagogical approaches and methods that ensure effective communicative development in the preschool educational process are highlighted.